2006
DOI: 10.1158/0008-5472.can-05-4679
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Induced and Spontaneous Carcinogenesis Is Increased in Fatless A-ZIP/F-1 but not in Obese ob/ob Mice

Abstract: Obesity is typically associated with increased tumor susceptibility, whereas caloric restriction, a regimen resulting in leanness, inhibits carcinogenesis. The link between adiposity and malignancies suggests that adipose tissue may influence carcinogenesis. An adipose tissue hormone, leptin, could be procarcinogenic because it stimulates proliferation in various tissues and tumor cell lines. Leptin may contribute to the correlation between adiposity and malignancies as its levels are usually increased in obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
1
13
1
Order By: Relevance
“…Our recent studies using the A-Zip/F-1 mice (18) that have no white adipose tissue and undetectable leptin, adiponectin, and other adipokines showed that these mice are more susceptible to papilloma formation in a classic two-stage skin carcinogenesis experiment (19), a finding confirmed in a separate report (20). Furthermore, when A-Zip/F-1 mice were crossed to the C3(1)/Tantigen mammary tumor transgenic mouse model, they developed larger and earlier tumors (19).…”
Section: Increased Cancer Risk In the Fatless A-zip/f-1 Mouse Modelmentioning
confidence: 52%
“…Our recent studies using the A-Zip/F-1 mice (18) that have no white adipose tissue and undetectable leptin, adiponectin, and other adipokines showed that these mice are more susceptible to papilloma formation in a classic two-stage skin carcinogenesis experiment (19), a finding confirmed in a separate report (20). Furthermore, when A-Zip/F-1 mice were crossed to the C3(1)/Tantigen mammary tumor transgenic mouse model, they developed larger and earlier tumors (19).…”
Section: Increased Cancer Risk In the Fatless A-zip/f-1 Mouse Modelmentioning
confidence: 52%
“…This hypothesis has been tested in two separate models. First, by chemically inducing skin carcinogenesis using DMBA and then promoting it with phorbol 12-myristate 13-acetate (PMA) and second, by exploring the effects of leptin deficiency in mice also deficient in the tumor suppressor gene p53 (Ablamunits et al, 2006). Contrary to the expected association between obesity and enhanced carcinogenesis, obese ob/ob mice did not develop induced skin papillomas and spontaneous p53-deficient malignancies at a higher rate than their lean littermates -suggesting that indeed low leptin levels do provide some protection from cancer, which could partially explain the beneficial effect of CR.…”
Section: Cancermentioning
confidence: 99%
“…Contrary to the expected association between obesity and enhanced carcinogenesis, obese ob/ob mice did not develop induced skin papillomas and spontaneous p53-deficient malignancies at a higher rate than their lean littermates -suggesting that indeed low leptin levels do provide some protection from cancer, which could partially explain the beneficial effect of CR. However, the effects of leptin are difficult to interpret because lipodystrophic (ZIP) mice that have both reduced leptin and low levels of adipose tissue were found to be highly susceptible to carcinogenesis (Ablamunits et al, 2006) indicating reduced leptin levels alone are unlikely to mediate the protective effect. Additionally, this role for leptin has been questioned (Brandon et al, 2009) by studies on the rate of melanoma tumor growth in lean and obese mice with leptin deficiency, or high levels of plasma leptin.…”
Section: Cancermentioning
confidence: 99%
“…A-ZIP/F-1 mice develop liver steatosis, which accounts for the increased body weight. These mice are also hyperglycemic, hyperinsulinemic, hyperlipidemic and hypertensive (Moitra et al, 1998;Ablamunits et al, 2006;Lamounier-Zepter et al, 2008).…”
Section: A-zip/f-1 Micementioning
confidence: 99%